Determinan Kinerja Karyawan Berdasarkan Kepemimpinan, Motivasi kerja dan Budaya Organisasi - Amin, Mohamad; Surijadi, Herman (Program Studi Administrasi Niaga STIA Said Perintah, 2022)
The purpose of this study was to determine and analyze the impact of leadership, organizational culture and work motivation on the performance of employees of internet service provider in Ambon City. The type of research used is explanatory research. The population in the study is all employees of an internet service provider in Ambon City. Sampling used a simple random sampling technique with a final sample of 34 employees. Data collection was carried out by distributing online questionnaire instruments that utilized the google form. The analytical tool used to answer the objectives of this study is multiple linear regression analysis. The research results prove that; leadership and work motivation have a positive and significant impact on employee performance. Another result is that organizational culture has a positive but not significant effect on the performance of employees of internet service provider in Ambon City.